Study of a release agents for a silicone mold on stone sculpture: Choice of release agent for carving silicone mold made in stone from Sierra Elvira - Bellido Márquez, María del Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
For the sculptural reproduction of a work carved in stone from Sierra Elvira by making a silicone mold, it has been necessary to study a release agent that improves the release of the silicone work and that it does not stain the stone material. Several release agents have been tested on stone specimens, the most suitable has been the charcoal fixative spray, which has helped to release the mold, in addition to protecting the work and applying a layer so thin that it hasn’t lost the register of the stone finish, being able to be removed by washing and brushing.